Pengenalan Basic Coding sebagai Upaya Penguatan Literasi Digital di SMP Negeri 1 Praya Tengah - Muhammad Imam Al Paqih; Muhammad Adriansyah; Ifan Hasnan Dani; Rida Alkausar Hardi; Fitrah Ramadhan; Rio Satriyantara; Maxtulus Junedy Nababan (Sinergi dan Harmoni Masyarakat MIPA, 2025)
This community service activity aims to enhance students’ digital literacy through the introduction of basic coding at SMP Negeri 1 Praya Tengah. Digital literacy is an essential competence in the era of information technology, encompassing not only the ability to operate digital devices but also the capacity to think logically, critically, and creatively in solving problems using technology. This program was implemented by the MBKM MAPS team from the Department of Mathematics, University of Mataram, involving seventh-grade students as participants. The implementation stages included preparation (coordination and planning), execution (introduction to basic coding concepts using the Python language on the Google Colab platform), and evaluation through pre-test and post-test to measure the program’s effectiveness. The results of the paired samples t-test analysis indicated a significant improvement in students’ abilities after participating in the training, with a mean difference value of  and a significance value of . These results demonstrate that the activity successfully improved students’ understanding of programming logic and computational thinking skills. In addition to the statistical improvement, observations showed high enthusiasm among participants in practicing simple coding tasks. Overall, this activity has had a positive impact on enhancing digital literacy and represents an initial step in fostering a technology-based learning culture within the school environment.